PENGEMBANGAN DESTINASI WISATA DESA GIRITENGAH UNTUK MEWUJUDKAN PARIWISATA BERKELANJUTAN - Titin Fatimah; Fransisca Iriani Roesmala Dewi; Endah Setyaningsih (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2022)
The Covid-19 pandemic that has hit the world since the end of 2019 has had a very significant impact. However, apart from the impacts and challenges posed by Covid-19, it turns out that there are positive opportunities for rural areas, because they have proven to be more resilient in facing difficulties during the pandemic. The Borobudur area is a world heritage area that needs to be preserved. Currently Borobudur is one of the 5 Super Priority Tourism Destinations set by the Ministry of Tourism and Creative Economy. Currently the tourism trend in the Borobudur area is starting to develop in the form of alternative tours to the surrounding villages. The problem is the current development and management for the 20 potential villages are insufficient. For this reason, a strategy is needed to develop villages in the Borobudur area to become qualified tourism destinations. One of these villages was chosen as the research locus/place, namely Giritengah Village. Based on previous research, it was found that Giritengah village has problems including: a lack of quality human resources and a lack of awareness and participation of residents. It can be seen the lack of harmony in the relationship between communities, so that it becomes an obstacle in managing village tourism. In addition, the lack of facilities to support tourism activities at each existing destination, so it is necessary to prepare tourist facilities to support comfort and safety, both during the day and at night. The aim of the research is to formulate the development concept of rural tourism destinations which includes designing tourism destination and its supporting facilities, and then strengthening tourism awareness behavior for the local community. The research method used: mixed qualitative and quantitative methods (mix-method). Data collection techniques used field observations, interviews, literature studies, Focus Group Discussions (FGD), questionnaires and simulations. The results obtained are an increase in the tourism awareness of the Giritengah community, tourism destination design, and area lighting design for selected destination. Keywords: destination development; tourist village; area lighting design; sustainable tourism; Borobudur Abstrak Pandemi Covid-19 yang melanda dunia yang terjadi sejak akhir 2019 memberikan dampak yang sangat signifikan. Namun, selain dampak dan tantangan yang ditimbulkan oleh Covid-19, ternyata ada peluang positif bagi pedesaan, karena terbukti lebih tangguh menghadapi kesulitan selama masa pandemi. Kawasan Borobudur merupakan sebuah kawasan world heritage yang perlu dilestarikan. Saat ini Borobudur menjadi salah satu dari 5 Destinasi Pariwisata Super Prioritas yang ditetapkan Kemenparekraf. Saat ini tren wisata di kawasan Borobudur mulai berkembang berupa wisata alternatif ke desa sekitarnya. Permasalahannya, pengembangan dan pengelolaan lebih lanjut untuk 20 desa di Borobudur belum optimal. Untuk itu diperlukan strategi pengembangan desa-desa di Kawasan Borobudur untuk menjadi destinasi pariwisata yang berkualitas. Salah satu desa tersebut dipilih sebagai lokus/tempat riset, yaitu Desa Giritengah. Berdasarkan riset sebelumnya ditemukan, Desa Giritengah memiliki permasalahan antara lain: kurangnya kualitas SDM pengelola dan kurangnya kesadaran dan partisipasi warga, dapat dilihat kekurangharmonisan hubungan antar komunitas, sehingga menjadi kendala dalam pengelolaan pariwisata desa. Selain itu, minimnya fasilitas penunjang kegiatan wisata pada masing-masing destinasi yang ada, sehingga perlu penyiapan fasilitas wisata untuk mendukung kenyamanan dan keamanan, baik wisata di siang hari maupun malam hari. Tujuan penelitian untuk menyusun konsep pengembangan destinasi wisata pedesaan yang meliputi penataan kawasan objek kunjungan, fasilitas pendukung, dan penguatan perilaku sadar wisata bagi pengelola dan masyarakat. Metode penelitian menggunakan metode gabungan antara kualitatif dan kuantitatif (mix-method). Teknik pengumpulan data menggunakan observasi lapangan, wawancara, studi literatur dan Focus Group Discussion (FGD), kuesioner dan simulasi. Hasil yang didapatkan adalah peningkatan sadar wisata masyarakat Giritengah, desain kawasan, dan desain pencahayaan kawasan destinasi terpilih.